2018
DOI: 10.1021/acsmedchemlett.7b00545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Screening of Pyrano[3,2-c]quinoline Analogues as Anti-inflammatory and Anticancer Agents

Abstract: A series of pyrano[3,2-]quinoline based structural analogues was synthesized using one-pot multicomponent condensation between 2,4-dihydroxy-1-methylquinoline, malononitrile, and diverse un(substituted) aromatic aldehydes. The synthesized compounds were evaluated for their anti-inflammatory and cytotoxicity activity. Initially, all the compounds were evaluated for the percent inhibition of cytokine release, and cytotoxicity activity and 50% inhibitory concentrations (IC) were also determined. Based on the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…In this study, development and in vivo efficacy evaluation of newly synthesized pyrano[3,2 c]quinoline derivatives as TNF‐α inhibitors are described. Based on the primary screening results (Upadhyay et al., ), the promising compounds ( 4f , 4i , 4j , and 4v ) were further evaluated for their in vivo efficacy using LPS and PDE4 and CIA assays in different mice/rat models. The outcome of the study revealed that 4v was found to be most the potent candidate of the series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, development and in vivo efficacy evaluation of newly synthesized pyrano[3,2 c]quinoline derivatives as TNF‐α inhibitors are described. Based on the primary screening results (Upadhyay et al., ), the promising compounds ( 4f , 4i , 4j , and 4v ) were further evaluated for their in vivo efficacy using LPS and PDE4 and CIA assays in different mice/rat models. The outcome of the study revealed that 4v was found to be most the potent candidate of the series.…”
Section: Discussionmentioning
confidence: 99%
“…Quinoline analogues exhibit diversified biological activities depending on the structure type (Kulagowski et al, 1994;Upadhyay, Dodia, Khunt, Chaniara, & Shah, 2018). As a part of number of natural products, 2,4-dihydroxyquinoline motifs are important compounds and exert a variety of interesting pharmacological properties (J, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Pyranoquinolones and fused pyrano [3,2-c]quinolone moities are widely available in bioactive natural products, synthetic products as well as pharmaceutical agents [2]. Pyrano [3,2-c]quinolones are primarily notable for their anticancer activity [3] [4], along with antimalarial [5], antibacterial [6], antiinflammatory [7], and antifungal [8] properties. Pyrano [3,2-c]quinolone is a core structural motif present in many alkaloids possessing important therapeutic activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrano[3,2‐ c ] quinolinones were found to be active against certain immuno‐reaction diseases, in particular against immediate hypersensitivity reactions (anaphylaxis) . A series of pyrano[3,2‐ c ]quinolines advertise skillful cell growth inhibition activity and are considered as potential anticancer agents . Rings annulated to the pyranoquinolinone unit showed potential medicinal properties such as antibacterial , anticoagulant , antitumor , and microtubule‐targeting agents .…”
Section: Introductionmentioning
confidence: 99%